Utilização de Realidade Aumentada no Desenvolvimento de Software Educacional: um exemplo em alguns conceitos na Astronomia - Santos, Maria Adélia Icó dos (2016)
In current times, the computer has been trying to, every day, make the reality that in a few years ago was considered a fiction. In this way, technicians and researchers have conducted studies in order to make it possible to expand and its cheapening, making them increasingly accessible and, consequently, popular. Today we have computers by submerging the various segments of society; homes and work environments are increasingly invaded by these cyberspace. The technology surprises with new equipment and software that some time ago were used separately. However, with the expansion and the growth that is happening in the world, the technology is moving in the direction of convergence, integration and multifunctional devices. As the computer is adapted to the different sectors of society, is entirely understandable and common accept that the school also make part of the globalized world and digital. Augmented Reality is a technology to introduce virtual objects with the real scenes. In this way, Virtual Reality and Augmented Reality can be considered as two areas directly connected with the new generations of the user interface, facilitating and enhancing the user's interactions with the computational applications. The use of Augmented Reality in the production of educational content contributes, notably, to facilitate learning because it makes an explanation more attractive and dynamic in relation to traditional forms of education. In spite of the Augmented Reality be used widely in various fields and areas of knowledge, mainly as a form of virtual tours that feature three-dimensional objects, has emerged a new generation of interface, to the extent that, using dimensional representations closer to the reality on the user, allows to break the barrier of the screen; in addition to interactions more natural. Astronomy is the science responsible for the study of the Universe, as it is constituted, and also for the formation of stars and their relations. Is the area of science that seeks to worry about the form, the distance, the greatness, in addition to the organization, origin, evolution, and still, composition and movement of all celestial bodies. Your study, particularly on the planets and the constellations, it is challenging for many students, however, it presents difficulties involve the identification and their relative positions that change constantly, throughout the year. Thus, the objective of this work is to develop an application (JMA - Memory Game in Astronomy) using the technology of Augmented Reality, facing the students of the first cycle of the initial series of Basic Education, applying it and analyzing the use of this tool; creating a differentiated situation in relation to process traditional educational and emphasizing the collaborative work.